Effect of Educational Intervention on Empowering the Sense of Empathy in Medical Students: Application of Health Belief Model - Mina Nezam Nia; Mahla Salajegheh (Kerman University of Medical Sciences, 2017)
Background and Objectives Empathy is one of the main skills in establishing a relationship between physicians and patients, and in order to increase this sense in students, it is necessary to introduce systematic and active programs into medical education. The aim of this study is to determine the effect of an educational intervention based on a health belief model on empowering the sense of empathy in medical students. Methods This was a quasi-experimental intervention conducted on two groups of 80 medical students involved in the internship program from Tehran University of Medical Sciences in 2015. Sampling was done randomly, and the subjects were randomly assigned to two groups, experimental and control. In the pre-test phase, all students completed a three-dimensional questionnaire including demographic data; a valid, reliable, and standardized Jefferson empathy questionnaire; and a section comprising questions designed by the researcher based on the constructs of the health belief model. Educational intervention was conducted only for the experimental group. To measure the results of educational intervention, the standardized patient questionnaires and the questionnaires completed by the students were used. Data were analyzed by means of frequency, percentage, mean and standard deviation, ANOVA, and independent t-tests. Results Before the intervention, the two groups were similar and comparable in terms of demographic variables. After the intervention, there was a significant difference in the mean scores of perceived susceptibility (P < 0.001) and perceived severity (P = 0.002) between the two groups. The mean scores of perceived barriers and perceived benefits were significant among the two groups (P < 0.001). In addition, there were significant differences in the constructs of self-efficacy and cues to action three months after intervention (P < 0.001). Conclusions Training based on the health belief model was effective in empowering the sense of empathy among medical students. Training on empathy skills is recommended in order to increase patient satisfaction, promote health outcomes, and increase job satisfaction among physicians.